The cost of leisure: the political ecology of the commercialization of Indonesia's protected areas. Issue 2 (3rd April 2022) - Purnomo, Mangku; Maryudi, Ahmad; Dedy Andriatmoko, Novil; Muhamad Jayadi, Edy; Faust, Heiko
ABSTRACT: Using the political ecology approach, we investigated the Indonesian government's decision to commercialize protected areas (PAs) and promote its tourism sector aggressively, and examined how this commercialization is enabled through various institutions and governing structures. We confirmed that the commercialization of PAs in Indonesia was an alternative accumulation, dealing with the crisis of capitalist accumulation. Our empirical finding showed that the commercialization of PAs in Indonesia had detimental environmental and social impacts, such as deadlocks or monopoly or management, and environmental deterioration. This commercialization pattern was different from accumulation by conservation in other regions, such as Africa, where local people were deprived of their access to the means of production, consequently becoming laborers in the tourism industry. In Indonesia, local people were given access to resources; however, as these resources were of little value, they became laborers in the tourism industry. Further research is needed to test whether different patterns of accumulation by conservation also apply to other types of PAs in Indonesia, such as national parks and customary forests, including various coral reef conservation areas in remote and small Islands used as tourist attractions.